O144 CALCIFICATION IN THE DESCENDING AORTA PREDICTS POSTOPERATIVE LEAKAGE OF INTRA-THORACIC ANASTOMOSIS AFTER OPEN ESOPHAGECTOMY FOR CANCER. (23rd November 2019) - Ukkonen, M; Wirta, E; Khan, J; Tyrväinen, T; Kechagias, A
Abstract: Aim: Postoperative anastomotic leakage is a major complication in the surgery of the esophagus. In this study, we aim to examine whether calcifications of the aortic segments can predict anastomotic leakage after open esophagectomy for cancer with intra-thoracic anastomosis of a gastric conduit. Background and methods: All patients with esophageal cancer who underwent elective esophagectomy with an intra-thoracic anastomosis at Tampere University Hospital between 2007-2018 were evaluated. Preoperative data were associated to outcome. These included demographic, anamnestic, clinical, laboratory, and radiologic data. Preoperative staging thoraco-abdominal CT-scans were re-evaluated to document the presence of calcifications in the various aortic segments. Results: A total of 97 patients (median age 64 (43-78) years, 20% female) were analysed, with anastomotic leakage occurring in 22 patients (23%). Median time from surgery to leakage was 10 (1-32) days, and follow-up time 28 (1-143) months. From all the factors that were evaluated in the univariate analysis, only the presence of calcification in the descending thoracic aorta was associated with a higher risk of anastomotic leakage (11% vs. 33%, HR 4.571; 95% CI 1.40-15.0; p=0.011). There was a trend for anastomotic leakage in the presence of calcification in the suprarenal abdominal aorta (13% vs. 29%, p=0.057). A higher leakage rate was documented when a calcification was present in the infrarenal abdominal aorta (8.3% vs. 25%, p=0.205), and in the ascending thoracic aorta (22% vs. 30%, p=0.559), without reaching statistical significance. Conclusion: The presence of a calcification in the descending thoracic aorta is associated with higher risk of anastomotic leakage after open esophagectomy for cancer.